PENINGKATAN HASIL BELAJAR SISWA DALAM PEMBELAJARAN IPS MELALUI MODEL PEMBELAJARAN QUANTUM TEACHING DI SEKOLAH DASAR - Sari, Padila (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2013)
The study was backed by the fact that in the 06 Taluak Elementary school learning IPS which for lerning, teacher was always a learning center and do not provide the opportunity for student to learn actively to explore their potential. For it was held a class action search, which aims to describe the learning result with Quantum teaching learning model using IPS. The result of this study showed an increase in : (1) The RPPcycle I with rate 73,18% rise on cycle II 92,85%, (2) implementation of teacher cycle I on average earned 67,31%, cycle II increased to 90,38%  and on aspect of student cycle I gained an average 66,34%, cycle II was a  very good criteria 90,38%, (30 Student Learning Outcomes on the cycle I with an average 73,06% increase ti 84,23% incycle II   Kata Kunci  :  hasil belajar, ips, model, quantum teaching, sd